Maize (Zea mays) intercropping in a silvopastoral system with Brachiaria hybrid cv. Mulato and Leucaena leucocephala cv. Peru - Iraola, Jorge; Mu??z, E.; Garc?a, Yenny; Hern?ndez, Jorge Luis; Moreira, E. (Cuban Journal of Agricultural Science, 2012)
The effect of maize (Zea mays) intercropping on the establishment of a simultaneous silvopastoril grass-leucaena sowing was studied. A completely randomized design with two treatments was used: A) Leucaena leucocephala cv Peru and Brachiaria hybrid cv. Mulato plus maize and B) leucaena plus mulato grass. Sowings were made at the beginning of June, 2007 in the rainy season, on a carbonated brown soil. Indicators studied were: number of plants, number of stalks plant-1, height and yield in leucaena and height, number of plants and yield in mulato grass. Botanical composition, availability and bromatological composition of the grassland were determined. SAS 9.1 software was used for the statistical analysis of the evaluated indicators. In treatment A, leucaena showed higher height values (P < 0.01) (108.67 cm vs. 93.73 cm), yield (P < 0.01) (90.20 vs. 75.10 g DM plants-1), number of stalks plant-1 (P < 0.001) (12.91 vs. 10.61) and number of plants (P < 0.001) (4.96 vs. 3.83). In this treatment, mulato grass showed higher number of plants (P < 0.01) (8.50 vs. 6.10) and yield (P < 0.001) (300.15 vs. 250.02 g DM plants.1). Percentage of mulato grass was also higher (66% vs. 50%) with this treatment. The remaining grasses did not differ. There was a higher availability (P < 0.05) in the treatment with maize (7.8 vs. 5.8 t DM ha-1). It is concluded that maize intercropping in a simultaneous sowing of leucaena and mulato grass favors leucaena establishment and does not affect the grass. Results indicate the possibility of establishing silvopatoral systems with leucaena and mulato grass of recent introduction in our country through maize intercropping in the sowings, with the advantage of grain harvesting and possible sale to cover the establishment expenses. Key words: leucaena, grass, simultaneous sowing, silvopastoril system